Purificação e estudos farmacológicos de uma nova neurotoxina proteíca da pele de Leptodactylus pentadactylus - Anjos, Falba Bernadete Ramos dos (1999)
The species Leptodactylus pentadactylus is an amphibian from the order anura, of the genre Leptodactylus which was find in the Indian, North and South American. A toxin was extracted from its skin secretion by column chromatograph DEAE-Cellulose and it presents convulsant activity by intravenous injections (i.v.) in rat and mice. The ffaction containing the purified toxin was eluted with 100 mM NaCl, dessalted, lyophilized and the resulting yellow-colored storage power was kept at - 25 °C. Its purity was evidenced in 6% polyacrilamide gel electrophoresis without SDS where was revealed only one major protein band; in presence of 10 % 2-mercaptoethanol and 1 % SDS; also only one protein band, corresponding to a molecular weigth of 65 KD was identified. After the purifícation, it was obtained -100 mg of pure toxin from lg of whole lyophilized venom. The toxin was inactivated at 100 °C for 5 min or after incubation with trypisin and quimotrypisin. In acute toxicity tests in male mouses in doses between 10 to 2000 pg/kg by i.v., caused symptons such as jumping, increased locomotor activity, walzing, defection, tonic-clonic convulsions and death. The LD50 and ED5o calculated was 560 ± 128 ug/kg and 230 ± 230ug/kg, respectively. The use of anticonvulsivants such as diazepam (10 mg/kg; i.m.) and fenobarbital (50 mg/kg; i.m.) in the rats before the use toxin (500 pg/kg), blocked the convulsions but not the death of these animais.